Study guides

☆☆

Q: 6 plus 4 3-8 2

Write your answer...

Submit

Still have questions?

Related questions

-3 + 4 - 6 + 3 - 2 + 42 = 1 - 6 + 3 - 2 + 42 = - 5 + 3 - 2 + 42 = - 2 - 2 + 42 = - 4 + 42 = 38

x2 + 13x + 4 = (x + 6½ + √38¼)(x + 6½ - √38¼). To find this, we need to find p and q, where p + q = 13, pq = 4. 4 = 42¼ - 38¼ = (6½ + √38¼)(6½ - √38¼); thus, p = (6½ + √38¼), q = (6½ - √38¼).

38

4 x 8 + 6 = 38

62 + 2 = 38

38

3 + 4 + 2 + 8 + 6 + 0.3 + 4 + 2 + 8 + 6 + 0.3 + 4 + 2 = 49.6

-6=-6(-a+2)+3(a-4)

(+4)+(+2)=(+6)

9 + 9 + 9 + 9 + 9 + 9 + 6 + 6 + 6 + 6 + 2 + 2 + 23 + 3 + 3 + 4 + 4 + 4 = 123

6 + A - 2 =6 - 2 + A = 4+A

-5-1 plus 4 plus 2-6 plus 4 is equal to -2

2

That will depend on the plus or minus values of 6 and 38 which have not been given.

2 + 3 + 4 + 5 + 6 = 20

2 + 4 + 6 + 8 + 0.300 = 20.300

6=4+2 6=6

4+2=6

-6 + 2 = -4

6 + -2 = 4

2 + 6 - 4 = 4

2 + 4 + 6 + 20 = 32

2+4+8+2+10+6 = 6+8+2+10+6 = 14+2+10+6 = 16+10+6 = 26+6 = 32

4+2=6

The simplified solution of 2/6 plus 1/6 plus 4/6 is 1 and 1/6.